Influence of skeletal muscle mass on ventilatory and hemodynamic variables during exercise in patients with chronic heart failure - Costa,Ricardo Vivacqua Cardoso (2003)
OBJECTIVE: To assess the influence of skeletal muscle mass on ventilatory and hemodynamic variables during exercise in patients with chronic heart failure (CHF). METHODS: Twenty-five male patients underwent maximum cardiopulmonary exercise testing on a treadmill with a ramp protocol and measurement of the skeletal muscle mass of their thighs by using magnetic resonance imaging. The clinically stable, noncachectic patients were assessed and compared with 14 healthy individuals (S) paired by age and body mass index, who underwent the same examinations. RESULTS: Similar values of skeletal muscle mass were found in both groups (CHF group: 3863 ± 874 g; S group: 3743 ± 540 g; p = 0.32). Significant correlations of oxygen consumption in the anaerobic threshold (CHF: r = 0.39; P= 0.02 and S: r = 0.14; P = 0.31) and of oxygen pulse also in the anaerobic threshold (CHF: r = 0.49; P = 0.01 and S: r =0.12; P = 0.36) were found only in the group of patients with chronic heart failure. CONCLUSION: The results obtained indicate that skeletal muscle mass may influence the capacity of patients with CHF to withstand submaximal effort, due to limitations in their physical condition, even maintaining a value similar to that of healthy individuals. This suggests qualitative changes in the musculature.